Assessment of Scoring Balloons in STEMI Patients Treated With DCB‐Only Angioplasty: A Single Center Study - Ioannis Merinopoulos; Natasha Corballis; Tharusha Gunawardena; U. Bhalraam; Rajkumar Natarajan; Johannes Reinhold; Upul Wickramarachchi; Clint Maart; Chris Sawh; Sreekumar Sulfi; Tim Gilbert; Trevor Wistow; et al. (Health Science Reports)
ABSTRACT Background and Aims A randomized trial has previously demonstrated that neointimal modification with a scoring balloon improves the anti‐restenotic effect of drug‐coated balloon (DCB) in patients with drug‐eluting stent restenosis. There are very limited data about the safety and efficacy of using scoring balloons as part of lesion preparation in patients with STEMI, especially in patients with de novo disease treated with DCB‐only angioplasty. Methods We undertook an analysis of the SPARTAN Norwich Registry to address this question. We compared the composite endpoint of cardiovascular mortality or unplanned target lesion revascularization in the DCB‐only cohort stratified based on the use or not of scoring balloon as part of the lesion preparation. Furthermore, we undertook a propensity score‐matched analysis of the DCB‐only cohort. Results A total of 452 consecutive patients were treated with DCB‐only angioplasty and scoring balloon was used in 121 patients as part of the lesion preparation. Scoring balloon was not a significant predictor of the composite endpoint even after propensity score‐matched analysis. Chronic obstructive pulmonary disease was the only significant predictor of the composite endpoint after propensity score‐matched analysis. Conclusion This is the first study demonstrating the safety and efficacy of scoring balloon as part of lesion preparation in patients with STEMI due to de novo disease treated with DCB‐only angioplasty. Trial Registration https://clinicaltrials.gov/ct2/show/NCT04482972; Unique identifier: NCT04482972.